2008
DOI: 10.1182/blood-2007-09-111971
|View full text |Cite
|
Sign up to set email alerts
|

Clonal heterogeneity in polycythemia vera patients with JAK2 exon12 and JAK2-V617F mutations

Abstract: We studied the lineage distribution of JAK2 mutations in peripheral blood of 8 polycythemia vera (PV) patients with exon 12 mutations and in 21 PV patients with JAK2-V617F. Using a quantitative allele discrimination assay, we detected exon 12 mutations in purified granulocytes, monocytes, and platelets of 8 patients studied, but lymphoid cells showed variable involvement and the mutation was absent in T cells. Endogenous erythroid colonies grew in all patients analyzed. One patient displayed erythroid colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 29 publications
6
85
1
Order By: Relevance
“…The excellent response to JAK2-inhibitors and the observations that bone marrow derived basophils and mast cells harbor the JAK2-mutation suggests an explanation: depending upon at which stage of hematopoietic development the mutation is introduced into the differentiation pathway, cells differentiate into differently affected cells such as granulocytes, monocytes, basophils, or platelets [26]. The occurrence of AP may depend upon whether or not there is a sufficient amount of JAK2-positive mast cells present in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent response to JAK2-inhibitors and the observations that bone marrow derived basophils and mast cells harbor the JAK2-mutation suggests an explanation: depending upon at which stage of hematopoietic development the mutation is introduced into the differentiation pathway, cells differentiate into differently affected cells such as granulocytes, monocytes, basophils, or platelets [26]. The occurrence of AP may depend upon whether or not there is a sufficient amount of JAK2-positive mast cells present in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…A number of patients with a simultaneous presence of JAK2-V617F and MPL-W515L/K, and JAK2-V617F and JAK2-ex12 mutations have been reported. 33,55 However, only one study proved that two independent clones of progenitors co-existed, one positive for JAK2-V617F and the other for JAK2-ex12 mutations. 96 Presence of del20q has been reported either as a mutation establishing clonal hematopoiesis before the acquisition of JAK2-V617F 44 or, in a different recent study, del20q-positive progenitors have been observed as a minor clone arising from JAK2-V617F-positive cells.…”
Section: Clonal Variability In Mpnmentioning
confidence: 99%
“…97 (f) A patient with polycythemia vera with both JAK2-V617F and JAK2-ex12 mutations was reported. 55 The two mutations were representing two clones of cells. (g, h) Simple clonal structure is likely in patients carrying a single MPL-W515L mutation.…”
Section: Genetic Complexity Of Mpn and Therapeutic Strategiesmentioning
confidence: 99%
See 2 more Smart Citations